From planning to performance: the adaptation process as a determinant of outcomes - Ramos-Villagrasa, P.; Passos, A. M.; García-Izquierdo, A. L. (Journal of Applied Behavioral Science, 2019)
Currently, teams require adaptation to deal with work demands successfully. However, research concerning team adaptation should necessarily involve a greater empirical effort in defining under which conditions teams prove more adaptable. This article seeks to contribute to the literature by linking plan formulation, plan execution, and team learning behaviors with team outcomes (i.e., team-adaptation perception and objective performance). Participants formed 142 teams, which were involved in structured-problem solving task (i.e. a simulated management competition). Conditional process analysis was used to test a double-mediated relationship. Results show that, although not all parts of the model are directly associated, there is an indirect link from plan formulation to team outcomes through plan execution and team learning behaviors. Our results support the idea of adaptation as a process, providing four ways in which organizations can elicit changes in teams: increasing plan execution, promoting team learning, improving team adaptive behaviors themselves, and building teams composed of members who demonstrate individual adaptability.